Isolasi dan Identifikasi Metabolit Sekunder dari Ekstrak Etil Asetat Batang Nangka (Artocarpus heterophyllus Lmk.) dan Aktivitasnya Sebagai Antibakteri: Isolation and Identification of Secondary Metabolite from Ethyl Acetate Extract of Jackfruit Stem (Artocarpus heterophyllus Lmk.) and Its Antibacterial Activity - Indriani; Iswan (KOVALEN: Jurnal Riset Kimia, 2020)
Isolation and identification of secondary metabolite of ethyl acetate extract of jackfruit stem (Artocarpus heterophyllus Lmk.) as well as its activity as antibacterial have been carried out. The purpose of this study was to know the characterization and antibacterial activity of secondary metabolites from ethyl acetate extract of the Jackfruit stem. Ethyl acetate extract was fractionated and purified using several chromatographic techniques. The identification of the isolated compound was elucidated by spectroscopic UV-Vis, IR, and NMR. Based on data analysis of UV, IR, and NMR spectra showed that the isolated compound was a flavonoid derivative. Antibacterial activity test of the isolated compound to Escherichia coli and Staphylococcus aureus was done by a well diffusion method. The inhibitory zone values of flavonoid compound in concentration series of 1000 µg/ml, 3000 µg/ml, and 5000 µg/ml against E. coli were 9.65 mm, 10.25 mm, and 11.00 mm, respectively. While, the inhibitory zone values in the same concentration series against S. aureus were 9.00 mm, 10.75 mm, and 11.38 mm. Keywords: Jackfruit, Artocarpus heterophyllus Lmk., flavonoid, antibacterial activity.